2012
DOI: 10.5120/9329-3634
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Metaheuristic Algorithm for Opinion Mining

Abstract: Opinion mining is a recent discipline combining Information Retrieval and Computational Linguistics which is concerned with the opinion a document expresses and not just with the topic in the document. Online forums, newsgroups, blogs, and specialized sites provide voluminous information feeds from where opinions can be retrieved. Opinion's polarity is established through application of machine learning techniques for classification of textual reviews as either a positive or negative class. In this paper, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Their results revealed that the Genetic Algorithm exhibits better performance than Naive Bayes, and that a combined classifier outperforms single classifiers. In addition, Saraswathi and Tamilarasi [19] proposed a modified metaheuristic algorithm for opinion mining, which uses Bagging to predict opinions as positive or negative. Their results revealed that Bagging performed better than Naive Bayes and the CART algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Their results revealed that the Genetic Algorithm exhibits better performance than Naive Bayes, and that a combined classifier outperforms single classifiers. In addition, Saraswathi and Tamilarasi [19] proposed a modified metaheuristic algorithm for opinion mining, which uses Bagging to predict opinions as positive or negative. Their results revealed that Bagging performed better than Naive Bayes and the CART algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…The weighted sum is then passed through an activation function, which determines the output of the neuron. The activation function introduces non-linearity into the model and allows neural networks to learn complex patterns and relationships (Saraswathi and Tamilarasi, 2012;Yang, 2022).…”
Section: Indicators For Estimation Research Parametersmentioning
confidence: 99%